2011
DOI: 10.1097/mao.0b013e31822e94f3
|View full text |Cite
|
Sign up to set email alerts
|

New Data on the Motion of the Normal and Reconstructed Tympanic Membrane

Abstract: Hypothesis The sound-induced motion of the tympanic membrane has features that are most consistent with modal responses to a uniform stimulus. Background Conceptual models of the coupling of tympanic-membrane motion to the ossicular chain can be classified as either modal responses to a uniform stimulation of the entire membrane, or traveling wave models in which sound energy is captured at the membrane’s rim and travels along the surface to the umbo. The stroboscopic holography technique we employ can separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…Spatial integration of forward sound power over the eardrum in the present two-component model comes from the fact that the acoustic pressure acts over the entire surface of the eardrum via its propagating and evanescent modes. The appearance of eardrum modal resonances at high frequencies in the present model is qualitatively consistent with experimental findings of multiple resonant modes of vibration of the tympanic membrane at frequencies above 8 kHz up to as high as 18 or 20 kHz (Rosowski et al, 2011;Cheng et al, 2010). These findings suggest independent motions of the manubrium relative to the remainder of the tympanic membrane.…”
Section: A Eardrum Model: Multiple Modes and Time Delaysupporting
confidence: 79%
“…Spatial integration of forward sound power over the eardrum in the present two-component model comes from the fact that the acoustic pressure acts over the entire surface of the eardrum via its propagating and evanescent modes. The appearance of eardrum modal resonances at high frequencies in the present model is qualitatively consistent with experimental findings of multiple resonant modes of vibration of the tympanic membrane at frequencies above 8 kHz up to as high as 18 or 20 kHz (Rosowski et al, 2011;Cheng et al, 2010). These findings suggest independent motions of the manubrium relative to the remainder of the tympanic membrane.…”
Section: A Eardrum Model: Multiple Modes and Time Delaysupporting
confidence: 79%
“…The traveling-wave-like motion could also be attributed to damped modal motion. These data were used to test various models and interpretations of TM motion in the literature, and were found to be consistent with the interpretation of de La Rochefoucauld and and others (Cheng et al, 2010;Rosowski et al, 2011). The contribution of these different motion patterns to ME function is a point of continuing study.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies have shown that sound-induced motions of the mammalian TM follow different patterns (simple, complex, ordered) within different stimulus frequency ranges . We have also suggested that the complex and ordered patterns result from the interaction of modal motions and traveling waves on the TM surface (Cheng et al, 2010;Rosowski et al, 2011). However, the magnitudes and wave numbers of the different modes of motion have not yet been quantified and questions, such as how modal motions and putative surface waves traveling on the TM surface are related to ME sound transmission, remain unanswered and need further investigation.…”
Section: B Measurements Of the Magnitude And Phase Angle Of Tm Motionmentioning
confidence: 99%
“…Recent studies by Rosowski et al reported clear signs of both modal TM responses and traveling waves on the human TM. 81,82 Characterization of the viscoelastic and dynamic properties [83][84][85][86] and 3D displacement patterns of the TM 87,88 to different sound frequencies is the first step to develop new anatomically accurate FE models, which could facilitate a better understanding of the complicated mechanics of sound reception by the ear. Surface measurement methods, such as laser Doppler vibrometry (LDV) and optoelectronic holography, provide quantitative information about the amplitude and phase of TM vibrations.…”
Section: Anatomy and Physiologymentioning
confidence: 99%